2014
DOI: 10.1007/s11523-014-0349-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of drug exposure with toxicity and clinical response in metastatic renal cell carcinoma patients receiving an attenuated dosing regimen of sunitinib

Abstract: An attenuated dosing (AD) regimen of 37.5 mg daily in repeated 4 week on, 2 week off cycles has been proposed to ameliorate frequent dose modifications caused by the toxicity observed with the approved dosing regimen of sunitinib for metastatic renal cell carcinoma (mRCC). This study aimed to determine the effect of drug exposure on toxicity and clinical response in patients receiving this regimen. All mRCC patients receiving AD sunitinib were invited to participate. In week 4 of each cycle, toxicity and plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
12
1
1
Order By: Relevance
“…Severe HFSR (grade ≥2) has been reported to be related to plasma drug concentration, cumulative drug area under the curve, and maintenance dose [21][22][23][24]. In the present study, no statistical difference was observed between non-HFSR and HFSR groups with regard to the initial doses patients received (data not shown).…”
Section: Discussioncontrasting
confidence: 60%
“…Severe HFSR (grade ≥2) has been reported to be related to plasma drug concentration, cumulative drug area under the curve, and maintenance dose [21][22][23][24]. In the present study, no statistical difference was observed between non-HFSR and HFSR groups with regard to the initial doses patients received (data not shown).…”
Section: Discussioncontrasting
confidence: 60%
“…Dose‐limiting and Grade ≥3 toxicities of sunitinib have been associated with total C min ≥100 ng/mL 17, 72. Grade ≥2 mucositis and altered taste have also been related to higher total C min 73. A relationship was also found between sunitinib AUC and Grade ≥3 toxicity ( P = 0.0005) 74.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 88%
“…Following Faivre et al, who described DLT at sum C trough ≥ 100 ng/mL, four other studies described a correlation between a high C trough and the occurrence of AEs . Two studies described treatment discontinuation for AEs at sum C trough > 75 ng/mL and > 100 ng/mL, respectively …”
Section: Methodsmentioning
confidence: 96%
“…DLT at sum C trough ≥ 100 ng/mL, four other studies described a correlation between a high C trough and the occurrence of AEs. 6,11,[40][41][42] Two studies described treatment discontinuation for AEs at sum C trough > 75 ng/mL and > 100 ng/mL, respectively. 40,41 Interestingly, toxicity also seems to be related to the country where patients are treated Lee et al described substantial differences in the incidences of various AEs between Asian patients who were treated in Asia or in countries outside of Asia.…”
Section: Clinical Thresholds For Responsementioning
confidence: 99%